Prevalence of work-related musculoskeletal disorders and ergonomic practice among dentists in Jeddah, Saudi Arabia - Meisha DE; Alsharqawi NS; Samarah AA; Al-Ghamdi MY (Dove Medical Press, 2019)
Dalia E Meisha,1 Nujud S Alsharqawi,2 Ahmad A Samarah,3 Mohammed Y Al-Ghamdi41Department of Dental Public Health, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 2Dental Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 3Department of Pediatric Dentistry, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi ArabiaBackground: Musculoskeletal disorders (MSD) is the second most common cause of disability. MSD due to the occupation are called work-related musculoskeletal disorders (WMSD) and are common among dentists.Objective: Assess the prevalence of self-reported work-related musculoskeletal disorders (WMSD) and to identify associated ergonomic practice among dentists practicing in Jeddah City, Saudi Arabia.Methods: Dentists practicing in Jeddah were invited to participate in this cross-sectional study using a self-administered survey. The survey consisted of 20 close-ended questions. The survey included questions regarding demographics, dental practice, general health status, exercising, ergonomic practice, musculoskeletal pain location, the severity of pain using a numeric pain rating scale (0–10), interventions sought, and missed work due to WMSD.Results: A sample of 234 dentists participated in this study. Prevalence of WMSD was found to be 70%. The most common location for WMSD pain was in the low back (85%) and neck (84.6%). Female dentists and dentists not exercising regularly had an increased risk of WMSD. The prevalence of CTS was 9%, and its risk increased with age and practicing in the private sector. Among the dental specialties, the least to report WMSD or CTS were maxillofacial surgeons and orthodontists. The reported ergonomic practice reached as low as 24%.Conclusion: Work-related musculoskeletal disorders and inadequate ergonomic practices were common. Ergonomics training intervention programs targeting dentists is suggested as a preventive measure for longer and healthier career lives.Keywords: musculoskeletal disorders, carpal tunnel syndrome, ergonomic, pain, dentist, Saudi